A STUDY ON THE ANTIBACTERIAL PROPERTIES OF GRAPHENE NANOMATERIALS AND GRAPHENE-BASED NANOCOMPOSITES - Lysander Aurelio, Robby
Bacterial contamination can cause various problems, especially in health and industry sector. However, excessive use of antibiotics and disinfectants can cause bacteria to become resistant. One method that can be used to overcome this problem is to use graphene-based nanocomposites, especially nanocomposites with graphene oxide (GO) and reduced graphene oxide (rGO). However, until now no researcher has directly compared the performance of the two nanocomposites. Therefore, the aim of this literature study is to determine whether the oxidation state of the graphene material in the nanocomposites affects its antibacterial properties. The literature study was carried out by collecting minimum inhibitory concentration (MIC) values of several types of graphene nanocomposites, particularly GO and rGO nanocomposites. Then the data will be made into a bubble chart to see the distribution of data and analyzed statistically by the one-way ANOVA with post-hoc Tukey HSD method to determine whether there is a significant difference in the antibacterial activity of the two nanocomposites. Statistical analysis was only performed on graphene nanocomposites with silver and zinc oxide which are the most studied nanocomposites. From the results of a literature study, it was found that the attachment of metal/metal oxide nanoparticles to a graphene surface was able to increase their antibacterial activity. Then, it was also found that there was significant difference in the antibacterial activity between of rGO-Ag with GO-Ag and AgNPs, while GO-Ag and AgNPs did not have a significant difference (P-value = 0.186). On the other hand, GO-ZnO had antibacterial activity that was significantly different from rGO-ZnO and ZnONPs, but rGO-ZnO had no significant difference with ZnONPs (P-value = 0.981). Therefore, it can be concluded that the oxidation level of graphene material can affect the antibacterial activity of graphene-based nanocomposites.